Monitoring of forest ecosystems (on the example of the Kabardino-Balkarian Republic) - Khuchunaev Buzigit; Kondratyeva Natalia; Dakhova Oksana; Kerefova Zalina; Shidugov Islam (BIO Web of Conferences, 2023)
The forest is one of the complex terrestrial ecosystems with landscape-geographic variability. The problem of anthropogenic influence on the environment in general and forest ecosystems in particular is steadily growing. The cause of pollution of all environments with the products of technogenesis, a decrease in biodiversity, a decrease in vegetation cover is most often human activity. The increasing anthropogenic impact on forest ecosystems over the years causes a decrease in their biological resistance and can lead to degradation and even complete destruction. The work studies forest ecosystems of the Kabardino-Balkarian Republic. The main forestforming rocks of the republic were identified. The age structure of the main forest-forming species has been determined. An analysis of the dynamics of the forest area by completeness, bonite classes was carried out.